PD‐L1 immunohistochemistry: Clones, cutoffs, and controversies. Issue 6 (3rd April 2022) - Chebib, Ivan; Mino‐Kenudson, Mari
Abstract : Cancer immunotherapy has become a major component of oncologic treatment for a growing number of malignancies. Of particular interest to pathology has been monoclonal antibody therapy targeting immune checkpoints, notably programmed cell death (PD‐1) and programmed cell death ligand (PD‐L1). Targeting of these checkpoints attempt to overcome tumor evasion of the immune system. While PD‐L1 testing is currently implemented as a predictive biomarker in multiple indications with the PD‐L1 axis blockade, PD‐L1 immunohistochemistry has been a complex issue for the pathology laboratory as it requires an understanding of multiple clones, on multiple testing platforms for multiple different malignancies, each with variable scoring criteria and thresholds. This review attempts to summarize the important PD‐L1 testing algorithms and test performance for the practicing pathologist who actively reviews PD‐L1 immunohistochemistry.